Asian rosewoods now critically endangered on IUCN Red List - Jalonen, Riina; Gaisberger, Hannes; Fremout, Tobias; Bounithiphonh, Chaloun; Kettle, Christopher (2024)
As a result of the revised conservation and threat assessment of highly valuable Asian rosewood species facilitated by the Alliance, the IUCN Red List was updated for the first time in over 20 years to include Asian Rosewoods as Critically Endangered. Additionally, the Laos government included actions to conserve the genetic resources of rare and threatened tree species, in its revised National Forestry Policy. This revision acknowledges that different species require different conservation and management actions and that ecosystem-level approaches are insufficient, particularly for highly threatened species.